Studies on Surface Morphology and Electrical Conductivity of PS Thin Films in Presence of Divalent Complexes (Baghdad Science Journal, 2019)
Optical properties and surface morphology of pure and doped Polystyrene films with different divalent metals of Zn, Cu and Sn and one concentration percentage have been studied. Measurements of UV-Vis spectrophotometer and AFM spectroscopy were determined. The absorbance, transmittance and reflectance spectrums were used to study different optical parameters such as absorption coefficient, refractive index, extinction coefficient and energy gap in the wavelengths rang 200-800nm. These parameters have increased in the presence of the metals. The change in the calculated values of energy gaps with doping metals content has been investigated in terms of PS matrix structural modification. The value of optical energy gap was found decreasing from 4.5eV of pure PS to reach 4.45, 4.38 and 4.32eV for Zn, Cu and Sn respectively. Measurement by AFM spectroscopy was done for two and three dimensional topographic images. From figures, the data of roughness average were 7.29, 7.31, 3.37 and 6.73nm for samples (Blank, Zn, Cu and Sn) respectively.